(untitled) (Journal of the College of Basic Education, 2023)
The development of this programme is highly significant to manage solid waste (SW) at different construction sites which also involved how resources are used as well as end-of-life deposition of materials in the waste stream. Ways to collect, recycle, transport, and dispose of SW that affects cost and environmental releases were looked at very carefully when this programme developed. Prior to 1970, sanitary landfills were very rare, SW was “dumped” and organic materials in the dumps were burned to reduce volume and this was common (1). This programme for today solid waste management is involving technologies that are more energy efficient and protective of human health and the environment. These technological changes and improvements have resulted from the needs to reduce direct impact on environment and residents living nearby construction sites. The programme developed so technology can be deployed and used to achieve the more efficient of saving resources, energy and above all environment protection